Analisis Risiko pada Usaha Kecil dan Menengah - Aulia, Salsa (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2023)
Small and Medium Enterprises (SMEs) play a significant role in the global economy by contributing to economic growth, job creation and increased innovation. However, SMEs often face unique challenges and risks, which can have a significant impact on the continuity of their operations. Therefore, risk analysis for SMEs is important to help them identify, manage and mitigate potential risks that can affect their business performance. This study aims to analyze the risks faced by SMEs, as well as to identify effective methods for managing and reducing these risks. This study also aims to provide a better understanding of the importance of risk analysis in the context of SMEs. This study uses a qualitative approach and descriptive method. The population in this study were street vendors in the Lampung area. Research data obtained through direct interviews. The results of the study show that the most common risks faced by SMEs include financial risk, operational risk, market risk, reputation risk and legal risk. In addition, this study also identified that effective methods of managing risk in SMEs include product or service diversification, efficient cash management, and sound business planning. Proper risk analysis can help SMEs identify these risks and take proactive steps to mitigate them, thus increasing the chances of their business success.